Generation of Core–Sheath Polymer Nanofibers by Pressurised Gyration - Mahalingam, Suntharavathanan (Polymers (Basel), 2020)
The ability to generate core–sheath bicomponent polymer nanofibers in a single-step with scale-up possibilities is demonstrated using pressurised gyration manufacturing. This is the first time that nanofiber containing more than one polymer having a core–sheath configuration has been generated in this way. Water-soluble polymers polyethylene oxide (PEO) and polyvinyl pyrrolidone (PVP) are used as the core and sheath layers, respectively. Core–sheath nanofibers with a diameter in the range of 331 to 998 nm were spun using 15 wt % PEO and 15 wt % PVP polymer solutions. The forming parameters, working pressure and rotating speed, had a significant influence on the size, size distribution and the surface morphology of the nanofibers generated. Overall, fibre size decreased with increasing working pressure and rotating speed. The fibre size was normally distributed in all cases, with 0.2 MPa working pressure in particular showing narrower distribution. The fibre size distributions for 0.1 and 0.3 MPa working pressure were broader and a mean fibre size of 331 nm was obtained in the latter case. The fibre size was evenly distributed and narrower for rotating speeds of 2000 and 4000 RPMs. The distribution was broader for rotating speed of 6000 RPM with a mean value obtained at 430 nm. Continuous, smooth and bead-free fibre morphologies were obtained in each case. The fibre cross-section analysis using a focused ion beam machine showed a solid core surrounded by a sheath layer. Our findings demonstrate that the pressurised gyration could be used to produce core–sheath polymer nanofibers reliably and cost-effectively with scale-up possibilities (~4 kg h(−1)).